2016
DOI: 10.1111/jcpp.12537
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Environmental exposures, neurodevelopment, and child mental health – new paradigms for the study of brain and behavioral effects

Abstract: Background Environmental exposures play a critical role in the genesis of some child mental health problems. Methods We open with a discussion of children’s vulnerability to neurotoxic substances, changes in the distribution of toxic exposures, and co-occurrence of social and physical exposures. We address trends in prevalence of mental health disorders, and approaches to the definition of disorders that are sensitive to the subtle effects of toxic exposures. We suggest broadening outcomes to include dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 208 publications
(243 reference statements)
2
83
0
2
Order By: Relevance
“…In this study, there was no overlap between the DMCs and DMRs detected in the adult and developmental exposure models, and the largest effects of dieldrin exposure were seen in the female developmental exposure. Supporting this data, previous studies have shown that the developing brain is particularly sensitive to environmental perturbations (Rauh and Margolis, 2016;Rice and Barone, 2000), and that environmental chemicals can act as potent neurotoxicants during development (Miodovnik, 2011;Heyer and Meredith, 2017). Furthermore, developmental exposures have the potential to modify epigenetic programming, which takes place during embryonic development (Reik et al, 2001;Feng et al, 2010;Marsit, 2015).…”
Section: Differences Between Adult and Developmental Exposuressupporting
confidence: 68%
“…In this study, there was no overlap between the DMCs and DMRs detected in the adult and developmental exposure models, and the largest effects of dieldrin exposure were seen in the female developmental exposure. Supporting this data, previous studies have shown that the developing brain is particularly sensitive to environmental perturbations (Rauh and Margolis, 2016;Rice and Barone, 2000), and that environmental chemicals can act as potent neurotoxicants during development (Miodovnik, 2011;Heyer and Meredith, 2017). Furthermore, developmental exposures have the potential to modify epigenetic programming, which takes place during embryonic development (Reik et al, 2001;Feng et al, 2010;Marsit, 2015).…”
Section: Differences Between Adult and Developmental Exposuressupporting
confidence: 68%
“…Ecosystems underpin all of our social and economic systems and feed back into them as well. This is demonstrated by a large body of work in the environment and health field that addresses a wide range of environmental determinants of health such as water quality and diarrhea (Levy et al, 2012), schistosomiasis (Stensgaard et al, 2013), exposure to pesticides (Rauh and Margolis, 2016), indoor air quality and respiratory health (Hulin et al, 2012), malaria (Bevilacqua et al, 2015), dengue (Fazidah A. Siregar et al, 2015), helminth-related diseases such as tapeworms and filariasis (Gazzinelli et al, 2012), and zoonoses such as leptospirosis (Mwachui et al, 2015) and avian influenza (Waltner-Toews, 2007).…”
Section: What Is Health?mentioning
confidence: 99%
“…Typically, studies have considered only a single component of neurodevelopment at a time, such as IQ or behavior. However, there are major conceptual advantages in jointly modeling domains of neurobehavioral development (Rauh and Margolis, 2016; Robinson, 2012). Accounting for the interrelations between developmental domains is more clinically relevant because neurological functions are mutually dependent.…”
Section: Introductionmentioning
confidence: 99%